Combat Against Grain Little Lice - N. S. Yangibayeva; R.S. Ro`zmetov; M.B. Doschonova; N.O.Raximova; G.Yo. Jumaniyozova (Zien Journals, 2024)
This article presents the types of aphids distributed in grain fields and the biological effectiveness of chemical preparations against them. Highly effective drugs are shown.
Keywords: aphids; wheat; millet; mospilan